GEOECONOMIC PERFORMANCE OF SUB-REGIONS IN SOUTH AMERICA: ELEMENTS FOR A NEW REGIONALIZATION - Cristovão Henrique Ribeiro da Silva; Arlindo Ananias Pereira da Silva; Juliana dos Santos Silva; Adriano Roberto Franquelino; Douglas Melo Fontes (Revista Tempo do Mundo, 2022)
The debate on economic development in the Amazon region has always been a delicate issue because it involves the complexity, biodiversity, potential and, paradoxically, the fragility of the biome. However, the anthropic occupation in the North of the South American continent advanced throughout the 20th century, with projects and proposals that urbanized and industrialized regional centers and, with the participation of the State, as a development vector for the region. With this scenario, the environment has always been a great regional asset in South America, and recently, the stage for regional integration initiatives such as the Iniciativa para a Integração da Infraestrutura Regional Sul-Americana (IIRSA), which largely represented the great integrationist project, throughout the second half of the decade of 2010, changes in global calibre alter the scope of decisions by nation-states, and by the end of 2019, the covid-19 pandemic changed the world with 197 million infected and 4.2 million dead. Still, with the hope brought about by vaccines, countries around the world have guided the action and management guidelines for a low-carbon economic recovery and reduction in the use of fossil fuels. In parallel to this, climate change has increasingly caused extreme natural events and has turned the attention of the international community to South America, and especially to Brazil, which since 2019 has adopted a disastrous environmental policy and erratic. With this panorama, regional experiences emerge, which we will call here geoeconomic performance, which certain spaces on the continent, and in Brazil, can incorporate into an agenda for the transition to a low-carbon economy. Here we present as a theoretical and methodological effort to understand the geoeconomic and geopolitical peculiarities of subnational governments in designing and adopting public policies (social, economic, territorial, and regional) capable of contributing to the ongoing changes in contemporary capitalism that is reorganizing itself for resumption, even with threats from new variants of SARS-CoV-2.